Formation of High‐Performance Multi‐Cation Halide Perovskites Photovoltaics by δ‐CsPbI3/δ‐RbPbI3 Seed‐Assisted Heterogeneous Nucleation. Issue 16 (15th March 2021) - Alharbi, Essa A.; Baumeler, Thomas P.; Krishna, Anurag; Alyamani, Ahmed Y.; Eickemeyer, Felix T.; Ouellette, Olivier; Pan, Linfeng; Alghamdi, Fahad S.; Wang, Zaiwei; Alotaibi, Mohammad Hayal; Yang, Bowen; Almalki, Masaud; et al.
Abstract: The performance of perovskite solar cells is highly dependent on the fabrication method; thus, controlling the growth mechanism of perovskite crystals is a promising way towards increasing their efficiency and stability. Herein, a multi‐cation halide composition of perovskite solar cells is engineered via the two‐step sequential deposition method. Strikingly, it is found that adding mixtures of 1D polymorphs of orthorhombic δ‐RbPbI3 and δ‐CsPbI3 to the PbI2 precursor solution induces the formation of porous mesostructured hexagonal films. This porosity greatly facilitates the heterogeneous nucleation and the penetration of FA (formamidinium)/MA (methylammonium) cations within the PbI2 film. Thus, the subsequent conversion of PbI2 into the desired multication cubic α‐structure by exposing it to a solution of formamidinium methylammonium halides is greatly enhanced. During the conversion step, the δ‐CsPbI3 also is fully integrated into the 3D mixed cation perovskite lattice, which exhibits high crystallinity and superior optoelectronic properties. The champion device shows a power conversion efficiency (PCE) over 22%. Furthermore, these devices exhibit enhanced operational stability, with the best device retaining more than 90% of its initial value of PCE under 1 Sun illumination with maximum power point tracking for 400 h. Abstract : A multi‐cation halide composition of perovskite solar cells is engineered via a two‐step sequential deposition method by adding mixtures of 1D polymorphs of orthorhombic δ‐RbPbI3 and δ‐CsPbI3 to the PbI2 . This approach greatly facilitates heterogeneous nucleation which leads to perovskite with high crystallinity and superior optoelectronic properties. Solar cells fabricated with these perovskites exhibit an efficiency of over 22%.